RELATION BETWEEN THE EARTH'S MAGNETIC FIELD INTENSITY AND GEOTECTONIC PROCESSES - Kurazhkovskii A.Y.; Kurazhkovskaya N.A.; Klain B.I. (My University, 2007)
Investigation of the relation between cyclic geomagnetic and geotectonic processes plays an important role in estimating the rate of energy transfer from the core–mantle boundary to the Earth’s surface layers and in studying mechanisms governing the dynamics of the lithosphere. The data on the magnetic polarity regime are used as a characteristic of the Earth’s magnetic field. The characteristic times of the reversal of magnetic polarity regimes and associated geotectonic processes are tens and hundreds of millions of years. The spectrum of variations in paleointensity (geomagnetic field intensity) characterized by periodicities from thousands to hundreds of million years undoubtedly contains more information about the processes related to the generation of the geomagnetic field.